Peptide mimetics of immunoglobulin A (IgA) and FcαRI block IgA‐induced human neutrophil activation and migration - Heineke, Marieke H. (Eur J Immunol, 2017)
The cross‐linking of the IgA Fc receptor (FcαRI) by IgA induces release of the chemoattractant LTB4, thereby recruiting neutrophils in a positive feedback loop. IgA autoantibodies of patients with autoimmune blistering skin diseases therefore induce massive recruitment of neutrophils, resulting in severe tissue damage. To interfere with neutrophil mobilization and reduce disease morbidity, we developed a panel of specific peptides mimicking either IgA or FcαRI sequences. CLIPS technology was used to stabilize three‐dimensional structures and to increase peptides’ half‐life. IgA and FcαRI peptides reduced phagocytosis of IgA‐coated beads, as well as IgA‐induced ROS production and neutrophil migration in in vitro and ex vivo (human skin) experiments. Since topical application would be the preferential route of administration, Cetomacrogol cream containing an IgA CLIPS peptide was developed. In the presence of a skin permeation enhancer, peptides in this cream were shown to penetrate the skin, while not diffusing systemically. Finally, epitope mapping was used to discover sequences important for binding between IgA and FcαRI. In conclusion, a cream containing IgA or FcαRI peptide mimetics, which block IgA‐induced neutrophil activation and migration in the skin may have therapeutic potential for patients with IgA‐mediated blistering skin diseases.